2020
DOI: 10.1101/2020.03.24.005413
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multiple loci linked to inversions are associated with eye size variation in species of theDrosophila virilisphylad

Abstract: 35The size and shape of organs is tightly controlled to achieve optimal function. Natural 36 morphological variations often represent functional adaptations to an ever-changing 37 environment. For instance, variation in head morphology is pervasive in insects and the 38 underlying molecular basis is starting to be revealed in the Drosophila genus for species of the 39 melanogaster group. However, it remains unclear whether similar diversifications are governed 40 by similar or different molecular mechanisms ov… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Our work provides new insights into ommatidia size regulation and the evolution of eye size. Together with evidence from other studies showing that changes in the timing of ey expression contributes to differences in ommatidia number in Drosophila (Ramaekers et al, 2019), we now have a better understand the genetic and developmental mechanisms that underlie the large diversity in Drosophila eye size (Arif et al, 2013; Buchberger et al, 2021; Gaspar et al, 2020; Hilbrant et al, 2014; Keesey et al, 2019; Norry and Gomez, 2017; Posnien et al, 2012; Ramaekers et al, 2019; Reis et al, 2020). Moreover, this evidence suggests that changes in the temporal expression of upstream TFs is a widespread mechanism responsible for morphological evolution.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Our work provides new insights into ommatidia size regulation and the evolution of eye size. Together with evidence from other studies showing that changes in the timing of ey expression contributes to differences in ommatidia number in Drosophila (Ramaekers et al, 2019), we now have a better understand the genetic and developmental mechanisms that underlie the large diversity in Drosophila eye size (Arif et al, 2013; Buchberger et al, 2021; Gaspar et al, 2020; Hilbrant et al, 2014; Keesey et al, 2019; Norry and Gomez, 2017; Posnien et al, 2012; Ramaekers et al, 2019; Reis et al, 2020). Moreover, this evidence suggests that changes in the temporal expression of upstream TFs is a widespread mechanism responsible for morphological evolution.…”
Section: Discussionmentioning
confidence: 76%
“…For example, killer flies, Coenosia sp., have evolved wider, flattened, anterior ommatidia to maximise contrast sensitivity and acuity as an adaptation to hunting (Gonzalez-Bellido et al, 2011). A number of studies have also found extensive variation in eye size within and between closely related species of Drosophila , caused by differences in ommatidia number and/or ommatidia area (Arif et al, 2013; Buchberger et al, 2021; Gaspar et al, 2020; Hilbrant et al, 2014; Keesey et al, 2019; Norry and Gomez, 2017; Posnien et al, 2012; Ramaekers et al, 2019; Reis et al, 2020). Despite the pervasive variation in eye morphology and detailed knowledge about eye development in Drosophila (Casares and Almudi, 2016; Casares and McGregor, 2021; Kumar, 2018), little is known about the genetic and developmental bases for variation in eye size even among Drosophila species with a few exceptions (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…But there has been extensive introgression between the X chromosomes of D. borealis and D. lacicola . Additionally, our data does not allow us to characterise or describe inversions despite their prevalence in the virilis group and their potential contribution to patterns of genomic divergence and speciation (Reis et al 2018, 2020).…”
Section: Discussionmentioning
confidence: 94%
“…Additionally, our data does not allow us to characterise or describe inversions despite their prevalence in the virilis group and their potential contribution to patterns of genomic divergence and speciation (Reis et al 2018(Reis et al , 2020 As with previous studies, we also observed a positive correlation between admixture proportion and absolute divergence across species pairs and genomic regions (Supplementary figure 6) (Stankowski et al 2019;Duranton et al 2020). In European lineages of sea bass, archaic genomic tracts were shown to contribute to excess absolute divergence and windows with high admixture proportions were also predicted to be involved in reproductive isolation (Duranton et al 2020).…”
mentioning
confidence: 98%
“…Additionally, our data do not allow us to characterize or describe inversions despite their prevalence in the virilis group (Reis et al. 2018, 2020).…”
Section: Discussionmentioning
confidence: 88%